From transition crises to macroeconomic stability? Lessons from a crises early warning system for Eastern European and CIS countries - Kristina Kittelmann; Marcel Tirpak; Rainer Schweickert; Lúcio Vinhas de Souza (Kiel Institute for the World Economy (IfW), 2006)
This paper uses a Markov regime-switching model to assess the vulnerability of a series of Central and Eastern European countries (i.e. Czech Republic, Hungary, Slovak Republic) and two CIS countries (i.e., Russia and Ukraine) during the period 19932004. For the new EU member states in Central and Eastern Europe, the results of our model show that the majority of crises in those countries can be explained by inconsistencies in the domestic policy mix and by the deterioration of macroeconomic fundamentals, as emphasized by first generation crises models, while for the CIS countries analysed, financial vulnerability type indicators were the most relevant, i.e., indicators connected with the second and third generation of crisis model better explain the vulnerability of these countries. Additionally, the set of indicators choosen by our model is rather heterogenous, supporting the superiority of a country-by-country approach.
Keywords: C22; F47; P20; 330; CIS; Early warning system; Currency crisis; Markov switching; Central and Eastern Europe; EU; Währungskrise; Frühwarnsystem; Markovscher Prozess; Schätzung; Tschechische Republik; Ungarn; Slowakei; Russland; Ukraine